2015
DOI: 10.3928/01477447-20151120-08
|View full text |Cite
|
Sign up to set email alerts
|

Medial Compartment Decompression by Fibular Osteotomy to Treat Medial Compartment Knee Osteoarthritis: A Pilot Study

Abstract: Compared with high tibial osteotomy and total knee arthroplasty, the authors found a simpler surgical procedure, partial fibular osteotomy, could effectively relieve knee pain and also correct the varus deformity for patients with medial compartment knee osteoarthritis (OA). From January 1996 to April 2012, a total of 156 patients with medial compartment OA were treated by proximal fibular osteotomy in the authors' hospital. A 2-cm-long section of fibula was resected 6 to 10 cm below the fibular head. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 20 publications
16
150
1
3
Order By: Relevance
“…The VAS pain score decreased by 96.9% compared with decreases of 42.4%, 40.4%, 9.0%, and 44.4% reported for treatment with lateral wedge insoles, acupuncture, knee braces and toe‐out gait modification, respectively. This finding supports the only other published report of upper partial fibulectomy for those with knee OA …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The VAS pain score decreased by 96.9% compared with decreases of 42.4%, 40.4%, 9.0%, and 44.4% reported for treatment with lateral wedge insoles, acupuncture, knee braces and toe‐out gait modification, respectively. This finding supports the only other published report of upper partial fibulectomy for those with knee OA …”
Section: Discussionsupporting
confidence: 92%
“…Recently, upper partial fibulectomy has been found to relieve pain and improve function of patients with medial compartment KOA. Yang et al used upper partial fibulectomy to treat 156 patients with medial compartment KOA; after more than 2 years follow‐up, proximal fibular osteotomy significantly improved both the radiographic appearance and function of the affected knee joint and led to long‐term pain relief. Chen et al studying the mechanism by which upper partial fibulectomy may benefit medial compartment KOA, suggested that upper partial fibulectomy caused the transfer of load from the medial to the lateral tibial plateau thereby resulting in pain relief.…”
mentioning
confidence: 99%
“…The following year, Yang et al [18] published the results of their retrospective series of PFO surgeries performed since 1996 at the Third Hospital of Hebei Medical University, Hebei, China. Zhang, who is the corresponding author of this study, in a separate interview, attributes the idea of PFO to one of his students from a rural hospital in China [19].…”
Section: Origin Of Proximal Fibular Osteotomymentioning
confidence: 99%
“…This has been called non-uniform settlement [20]. When the medial side "settles" down, there is side-slipping of the femoral condyle medially during walking and playing sports which aggravates the non-uniform settlement due to excessive loads on the medial side [18].…”
Section: The Concept Of Non-uniform Settlementmentioning
confidence: 99%
“…The PTFJ has largely been neglected for its contribution to the knee joint 14 . However, in recent years, it has been reported that proximal fibular osteotomy could be regarded as an effective surgery for pain relief and improvement of medial JSN and function in patients with medial tibiofemoral knee OA 15,16 . Therefore, exploration of the role of PTFJ in knee OA is of interest and there is a substantial need to develop techniques to measure PTFJ.…”
Section: Table VImentioning
confidence: 99%